High frequency of severe dengue cases during the American/Asian DENV-2 lineage II epidemic in Peru - Durand, Salomon (2022)
Introduction. The entry of American/Asian DENV-2 lineage II in the Loreto region of the Peruvian Amazon coincided with a sudden increase in dengue cases requiring hospitalization. However, official statistics reported few severe cases. It is postulated that there was an underreporting of severe cases in the official reports of the Ministry of Health. Objectives. To determine the frequency of patients with signs of severity among patients hospitalized for probable dengue fever during the 2011 outbreak at the Iquitos Hospital, Peru. Methods. A longitudinal study was carried out applying a daily checklist on the presence of signs of severity during hospital stay to a group of patients hospitalized in the dengue unit of the Iquitos hospital. Results. Of 178 patients evaluated, 66 (37%, CI: 29.9- 44.6%) presented some sign of severity, mostly due to shock (75,7%). This result contrasts with the number of patients with severe dengue reported by the Ministry of Health during 2011 in the Loreto region. Conclusion. Approximately one third of the patients who were hospitalized with a diagnosis of dengue during the outbreak of American/Asian DENV-2 lineage II developed signs of severity during their hospitalization.